2019
DOI: 10.3389/fimmu.2019.02389
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Induces Interleukin-17A Expression on Th17 Cells and CD4+ Regulatory T Cells as Well as Platelet Dysfunction

Abstract: Background: The organism's immune response to trauma is distinctively controlled, its dysregulation leading to severe post-traumatic complications. Platelets, CD4+ regulatory T cells (CD4+ Tregs) and T helper 17 (Th17) cells have been identified to participate in the post-traumatic immune response. Unfortunately, little is known about their exact role and potential interdependency in humans. Aims of this clinical trial were to phenotype the human immune response following injury and to identify risk factors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
5
11
0
Order By: Relevance
“…The multiple trauma patients showed statistically significant higher interleukin-17A plasma concentrations throughout the observation period, as compared to the control group. This is in line with the work of Abboud [49]. In this study, the multiple trauma patients with MOF showed statistically significant higher IL-17A concentrations at the time points 0 h, 48 h and 72 h, as compared to the trauma patients without MOF.…”
Section: Interleukin-17asupporting
confidence: 91%
“…The multiple trauma patients showed statistically significant higher interleukin-17A plasma concentrations throughout the observation period, as compared to the control group. This is in line with the work of Abboud [49]. In this study, the multiple trauma patients with MOF showed statistically significant higher IL-17A concentrations at the time points 0 h, 48 h and 72 h, as compared to the trauma patients without MOF.…”
Section: Interleukin-17asupporting
confidence: 91%
“…This is in line with the work of Abboud et al, who highlighted the importance of IL-17A in the post-traumatic immune response in patients with a severe blunt trauma [46]. Furthermore, Hefele et al discovered an increased IL-17A expression on TH-17 cells and CD4 + Tregs following trauma [47]. In this study, the multiple trauma patients with MOF showed statistically signi cantly higher IL-17A concentrations at the time points 0 h, 48 h and 72 h, as compared to the trauma patients without MOF.…”
Section: Interleukin-17asupporting
confidence: 85%
“…NK/NKT cells are also lowly expressed in PBMCs compared to T helper cell subsets (62), and in addition, NK cells do not normally express T cell-associated CD3. Collectively, these observations strongly suggest the source of increased IL-17A in PTSD patients is most likely derived from CD4+ Th17 cells, which is supported by a report from Hefele et al which showed trauma can increase IL-17A specifically in Th17 subsets (63).…”
Section: Discussionsupporting
confidence: 67%
“…Collectively, these observations strongly suggest the source of increased IL-17A in PTSD patients is most likely derived from CD4+ Th17 cells, which is supported by a report from Hefele et al. which showed trauma can increase IL-17A specifically in Th17 subsets ( 63 ).…”
Section: Discussionsupporting
confidence: 65%